On the accuracy of palaeopole estimations from magnetic field measurements. Issue 3 (25th September 2017) - Vervelidou, F; Lesur, V; Morschhauser, A; Grott, M; Thomas, P
Summary: Various techniques have been proposed for palaeopole position estimation based on magnetic field measurements. Such estimates can offer insights into the rotational dynamics and the dynamo history of moons and terrestrial planets carrying a crustal magnetic field. Motivated by discrepancies in the estimated palaeopole positions among various studies regarding the Moon and Mars, we examine the limitations of magnetic field measurements as source of information for palaeopole position studies. It is already known that magnetic field measurements cannot constrain the null space of the magnetization nor its full spectral content. However, the extent to which these limitations affect palaeopole estimates has not been previously investigated in a systematic way. In this study, by means of the vector Spherical Harmonics formalism, we show that inferring palaeopole positions from magnetic field measurements necessarily introduces, explicitly or implicitly, assumptions about both the null space and the full spectral content of the magnetization. Moreover, we demonstrate through synthetic tests that if these assumptions are inaccurate, then the resulting palaeopole position estimates are wrong. Based on this finding, we make suggestions that can allow future palaeopole studies to be conducted in a more constructive way.